A methodical approach for the assessment of waste sorting plants. Issue 2 (February 2017) - Feil, Alexander; Pretz, Thomas; Vitz, Philipp; Thoden van Velzen, Eggo Ulphard
A techno-economical evaluation of the processing result of waste sorting plants should at least provide a realistic assessment of the recovery yields of valuable materials and of the qualities of the obtained products. This practical data is generated by weighing all the output products and sampling these products. Due to the technological complexity of sorting plants, for example, lightweight packaging waste treatments plants and the high expenditures concerning time and costs of sampling with subsequent manual sorting for quality determination, usually only final products undergo such an investigation. Thereby, the transferability of the results depends decisively on the boundary conditions (extent, throughput of the plant, process parameterization). Given that the process is too complex, not all relevant information of the process steps can be determined by sampling. By model calculations and/or adjustment of reasonable assumptions, information concerning weak points in the process can be identified, which can be used for further plant optimization. For the example of the recovery of beverage cartons from co-collected and mechanically recovered mixtures of lightweight packaging waste, a methodical approach for the assessment of processing results will be presented.